Co-Designing an Intervention to Increase HIV Testing Uptake with Women from Indonesia At-Risk of HIV: Protocol for a Participatory Action Research Study. - Gray, Corie; Crawford, Gemma; Lobo, Roanna; Maycock, Bruce (2019)
Early diagnosis is a critical component of the global response to the human immunodeficiency virus (HIV). In Australia, more than two-thirds of women from Southeast Asia are diagnosed late with HIV. There is limited evidence regarding the barriers to HIV testing and which interventions work to increase an uptake among migrants living in high-income countries. This participatory action research (PAR) project will work with women from Indonesia to co-design an intervention to increase HIV testing uptake in Western Australia. The project will involve trained community researchers, representatives from relevant organizations, and community women born in Indonesia. We will conduct three PAR cycles. Phase one will use focus groups to understand enablers for HIV testing among community members. In phase two, data will be presented back to members of the participating communities who will be invited to co-design an intervention to increase HIV testing. The final cycle will focus on implementing and evaluating the resulting intervention. This project will add to the small body of literature on pathways and enablers to HIV testing, and to new insights regarding interventions that work for women from migrant communities and why.